(untitled) (PANGEEA, 2025)
The mountainous population of the Alba country is facing a serious economic problems: lack of jobs due to stop mining activity. The paper seeks an alternative presentation for the unemployed in the region, tourism. The proposal is based on an analysis of natural and anthropogenic tourism potential in the area of Metalliferi-Trascau-Bihor Mountains situated in Alba County. Is presented the potential of agro-tourist, cultural tourism, sport, leisure and spas.